PEMBELAJARAN TECHNOLOGICAL PEDAGOGICAL AND CONTENT KNOWLEDGE (TPACK) PADA PENDIDIKAN AGAMA ISLAM - Susi Siviana Sari (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2022)
Islamic Education is an education that Fardhu to be taught to students. The development of an increasingly advanced age, then an educator must also adjust learning according to the needs of students in this digital era. Learning Technological Pedagogical and Content Knowledge (TPACK) is very suitable for use by educators in the current digital era, so that educators and students can feel the learning of learning in integrating between learning and technology. The research method used by the author is a literature research, the data collected obtained through journal studies, books, documents relevant to the problem of research. The results of this study indicate that the Technological Pedagogical and Content Knowledge (TPACK) is a combination of three components, namely: technology, pedagogy and content in learning. The intersection between the three components of knowledge produces a learning model that can achieve learning goals, one of which increases students' creative thinking skills. The implementation of the Pedagogical and Content Knowledge Technological (TPACK) in Islamic Education starts from educators who must create a Learning Implementation Plan (RPP) first, then applied in learning activities by integrating technology, pedagogy and learning content. Keywords: Learning, TPACK, Islamic Religious Education